Cloud Computing With Green Virtual Systems: Optimizing Resource Utilization in Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In cloud computing, systems require a hardware inventory that is often prohibitive in terms of cost and manpower involved in its installation and configuration. In addition, physical servers in general are highly underutilized and remain powered on 24 by 7 regardless of the extent of their utilization. This is highly inefficient given on average servers are underutilized and use only 10% of the overall resources of the server.This goal of this research is to create cloud systems that are “leaner” or more efficient in terms of their use of resources in terms of time and the quantity used. A “Green” cloud system responds to peak utilization periods and adjusts availability of resources based on them expanding or shrinking the cloud as needed. Furthermore, this system will detect the nature of the demand on it and provide customized resources specific to the needs of the services required by the users of the cloud. For example, more if more processor-intensive applications are in demand, the amount of processor resources will dynamically increase to support the demand.